If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-0.33x-0=3
We simplify the equation to the form, which is simple to understand
-0.33x-0=3
We move all terms containing x to the left and all other terms to the right.
-0.33x=+3
We simplify left and right side of the equation.
-0.33x=+3
We divide both sides of the equation by -0.33 to get x.
x=-9.09090909091
| 6y(6y-3)+15y= | | 16-4(c+3)= | | 0.8x+0.26x=40150 | | 3xy-4xy+2y= | | 12x+x-6=0 | | -0.33(0)-y=3 | | x^2-x-2=-4x-4 | | 12x+x=6 | | 48x^2+10x-25=0 | | 15(3+x)=75 | | 4(-x-2)-1(2-5x)=1 | | 8+4k=-10+x | | x^2+5x-5=9 | | 12x+9=141 | | x^2-13x+1=0 | | 4(-x-2)-1(-5x+2)=1 | | y=x^2-3x-9 | | x^2-4x-48=0 | | 7.5(3x+9)(8x+7)=0 | | 1.5t-1=1.7t-5 | | 7.5(3x+9)(8x+7)= | | 4(-x-2)-1(1-5x)=1 | | 2d+6-3d=-4 | | 2(5y-7)=3(y+4) | | 4x^2+24x+64=0 | | 16x=400 | | 0=3.5x-6 | | (2x+6)+(2x+1)=4(x-1)+9 | | y=0-6 | | x(0.8y)+1.3x(0.2y)=40150 | | 0.8747x+231.06=0 | | 6(x+3)-3x=3(x+1)+15 |